Tortura e Migrazioni/Torture and Migration, by Fabio Perocco (ed.) - Iside Gjergji (Torture)
Reviewing this volume edited by Fabio Perocco and published in open access version by University of Venice Ca’ Foscari Editions is no easy task. What makes it hard to sum up this work is not its length (430 pages), but rather its interdisciplinary approach, the depth of observations, the richness in contents and points of view, its geographical width. Yet, these aspects make the book fundamental for anyone willing to understand migratory movements in today’s world. Its main merit is having addressed, consistently and systematically, the close relation that has come to be, over the course of decades, between torture and migration. Such relation is no recent piece of news: for a long time, torture has been indicated as one of the most widespread reasons for leaving, one of the most frequent experiences lived along the migration path and, more and more often, a reality that migrants are forced to tackle in receiving countries. Nevertheless, the scientific narrative of such relation is often limited, fragmented and, sometimes, manipulated. Torture has thus far been studied systematically in relation to power (MacMaster 2004), wars and dictatorships (Hajjar 2013, Cohen 2005, Rejali 2009), it is considered as lying at the basis of modernity (Reemtsma 2012) or of the process of civilization (Linklater 2007), but never before it had been analyzed as a structured element of migration. Thus, the volume deserves to be recognized as paving the way for an innovative field of research.